CORRELATION BETWEEN ENTEROBIASIS vermicularis prevalence hygienes WITH INDIVIDUAL IN CHILDREN AGED 5-18 YEARS IN VILLAGE SUB KARANGASEM Kutorejo MOJOKERTO DISTRICT - Heru Setiawan; Mas Mansyur; E. Devi Dwi Rianti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Enterobiasis vermicularis parasitic worm infection is a disease characterized by typical symptoms of pruritus ani and other nonspecific symptoms include nausea, abdominal pain, decreased appetite, weight loss and enurisis. Villagers Karangasem district Kutorejo Mojokerto district, taking water from rivers and wells Cangkring times to support its activities. This is an effective way as a medium of transmission besides hygienes Enterobiasis individual was instrumental in the transmission of this disease. From the research we are doing there is a significant correlation between the prevalence Enterobiasis vermicularis with individual hygienes in children aged 5-18 years in the village ofKarangasem district Kutorejo Mojokerto regency, with a count of 98.08 whereas X2 X2 table = 3.84, besides the factor age, sex and education level also affected.